E-I balance and human diseases - from molecules to networking - Eichler, Sabrina A.; Meier, Jochen C. (Frontiers in Molecular Neuroscience, 2008)
Information transfer in the brain requires a homeostatic control of neuronal excitability. Therefore, a functional balance between excitatory and inhibitory systems is established during development. This review contains recent information about the molecular mechanisms orchestrating the establishment and maintenance of this excitation-inhibition (E-I) balance, and it reviews examples of deregulation of inhibitory and excitatory systems at a molecular, network and disease level of investigation.